High throughput quantitative analysis of melamine and triazines by MALDI-TOF MS - Singh, Ajeet; Panchagnula, Venkateswarlu (Analytical Methods, 2011)
Quantitative and high throughput MALDI MS analysis of symmetrical triazines (s-triazines), and milk contaminated with melamine has been demonstrated. s-Triazines from a multi component aqueous test mixture, and melamine, a known adulterant in milk, were quantified at low parts-per-million (ppm) level using 2,5-dihydroxybenzoic acid (2,5-DHB) as a matrix. Mass spectral peak intensity ratios of the analyte and a suitable internal standard were used for the quantitation. Limit of detection at 20 `parts-per- billion' (nano molar concentration) has been achieved for the s-triazines from the aqueous mixture. Quantitation from MALDI MS peak intensities was validated using LC-PDA and LC-ESI-MS analysis using both spectral peak intensities and areas under the chromatographic curves. Excellent linearity in low ppm concentrations along with good precision and accuracy, all of which were comparable to LC-ESI-MS data, were obtained with the advantage of rapid analysis.

Matrix-assisted laser desorption/ionization mass spectrometry analysis of dimethyl arginine isomers from urine - Bhattacharya, Nivedita; Singh, Ajeet; Ghanate, Avinash; Phadke, Gayatri; Parmar, Dharmesh; Dhaware, Deepika G.; Basak, Trayambak; Sengupta, Shantanu; Panchagnula, Venkateswarlu (Analytical Methods, 2014)
Isomeric asymmetric and symmetric dimethyl arginine (ADMA and SDMA respectively) residues are excreted in urine and are putative markers of cardiovascular and chronic kidney diseases. In this work, we demonstrate simultaneous and quantitative detection of endogeneous ADMA and SDMA from urine samples of healthy subjects using MALDI-TOF MS without any chromatographic separation. The DMA isomers yielded [M + H](+) ions along with their product ions formed due to MALDI in-source fragmentation. The precursor ions were validated using MALDI-TOF MS/MS as well as direct injection ESI-Q-TOF MS/MS. ADMA and SDMA generated unique product ions at similar to m/z 46 and similar to m/z 172 respectively in the MS-mode itself. These were advantageously used for full scan-mode absolute quantification of the isomeric metabolites. The m/z observed for all the ions was within 10 ppm mass accuracy. The calibration method was established by generating internal standard normalized peak area-based concentration response curves using synthetic standards. Good linearities (R-2 > 0.95) with acceptable intra-assay, inter-assay variation (within 15% RSD) and excellent recoveries were observed for quality control samples. Finally, endogeneous concentrations of the metabolites were determined in urine from healthy subjects (n = 11). ADMA and SDMA were found to be in the range of 1.6-8 mu M and 2.9-9.1 mu M in urine and were in agreement with previously reported physiological levels.

Determination of triazines and triazoles in grapes using atmospheric pressure matrix-assisted laser desorption/ionization high-resolution mass spectrometry - Mahale, Vishal; Singh, Ajeet; Phadke, Gayatri S.; Ghanate, Avinash D.; Oulkar, Dasharath P.; Banerjee, Kaushik; Panchagnula, Venkateswarlu (Journal of Aoac International, 2017)
A chromatography-free atmospheric pressure matrix-assisted laser desorption/ionization high-resolution mass spectrometry (AP-MALDI HRMS) method is described for the simultaneous and quantitative detection of triazines and triazoles in grapes. The analytes were detected reproducibly with high mass accuracy (mass error within 5 ppm) and further confirmed by collision-induced dissociation fragmentation in tandem MS. The LODs and LOQs for all the analytes were found to be in the nanogram per gram level (15-20 ng/g LOQ). Internal standard normalized high-resolution accurate mass extracted (HR-AM) peak intensities of the detected ions were used to generate the concentration response curves. Linearity (with R-2 values around 0.99) was obtained for these curves within a concentration range of 20-200 ng/g of the individual analytes. The accuracy and precision of the method were further established using QC samples. Validation and performance comparison of the AP-MALDI HRMS method with an existing standard method using LC with :triple quadrupole MS was carried out (evaluating sensitivity, accuracy, precision, and analysis time) using 20 table-grape field samples after QuEChERS extraction.

Polymer graphene-based nanofibers and their application for batteries - Mishra, Sasmita; Singh, Sandip; Singh, Ajeet (Electrospinning of Graphene, 2021)
Polymer graphene-based nanofibers are increasingly used in energy storage devices, especially in lithium-ion batteries and thus attracting more and more industrial and academic research in material chemistry. Metal-doped graphene-based polymer nanofibers are now gaining much attention and recently are successfully used in related energy storage devices, including supercapacitors and more. This chapter primarily focuses on a brief of nanofibers, electrospinning and graphene followed by the review of polymer graphene-based nanofibers in the present scenario.